Prevalence of tick infestation (Rhipicephalus sanguineus and Hyalomma anatolicum anatolicum) in dogs in Punjab, Pakistan - Manzoor Hussain (Veterinaria Italiana, 2012)
This study was conducted to identify ticks that infest dogs in the Rawalpindi region of Punjab, Pakistan. A total of 525 dogs were examined between June and September 2010. Of these, 60 (11.42%) were infested with ticks. The morphological features of the ticks were identified by using a stereomicroscope to confirm their identity using morphological keys. Two species were observed, namely: Rhipicephalus sanguineus and Hyalomma anatolicum anatolicum. The prevalence rate of these species was 98.33% and 1.66%, respectively. Of the 508 specimens collected, 265 male, 224 female ticks and 19 nymphs were identified. No larvae were collected from the infested dogs during the study period. There was no significant difference observed during the study months.